ORGANIZATIONAL AND ECONOMIC MECHANISM OF MANAGEMENT OF SOLID MUNICIPAL WASTE MANAGEMENT SYSTEM - A. Kirillova; N. Musinova (Вестник университета, 2018)
The modern system of solid municipal waste management has characterized by the fact that their volumes are continuously increasing and almost completely exported to landfills, that significantly deteriorating the sanitary condition of the territories. One of the main directions in the field of complex system of solid municipal waste management formation is the development of organizational and economic mechanism of management of solid municipal waste management system. The article considers the components of the organizational and economic mechanisms in the system of solid municipal waste management and their interconnection with legal and informational mechanisms. At the same time, attention has focused on those tasks that need to be solving to improve the efficiency of the organizational and economic mechanism of management of solid municipal waste management system.